Lugud Tarlac tourism and community center - Dela Vega, Marion Gail D.C.; Rinen, Richard Martin E. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The comprehensive design project is an agenda-based design. Tarlac province as a macro-site is selected first by the designer, and information about it is gathered. The data is gathered through personal observations and legal documents of the city and province (CLUPs and development plans). Issues and concerns are collected and analyzed forming the four main agenda of the project: Culture and tourism, community development, livelihood and commerce, and recreational enhancement. After defining the agenda, a micro-site fitted for it is chosen. In this case, Brgy. Tibag within Tarlac City is chosen. The selected micro-site is ideal because it is not a part of the city proper or poblacion, hence the density if the area is not too high. However, it is only a kilometer from the poblacion area, which makes it still accessible to a large number of people. The goal of the project is to improve the tourism in the province while also considering its people and environment. In the project, it will be shown how spaces generated from the agenda is integrated with each other through its common goals and functionality. Tarlac's tourism and community center is established.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Tourism -- Tarlac -- Philippines